2022
DOI: 10.55933/pjga.v2i2.307
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Massase Olahraga Sebagai Pemulihan Pasif Terhadap Peningkatan Vo2max Atlet Bolavoli

Abstract: Penelitian ini bertujuan untukmengetahui massase olahraga dalam pemulihan pasif setelah latihan dalam meningkatkan vo2max atlet bolavoli. Metode yang digunakan dalam penelitian ini adalah metode eksperiment dengan sebuah design menggunakan randomized control group pretest-posttest. Dimana kelompok eksperiment mendapat perlakuan berupa massase olahraga sebagai pemulihan pasif setelah latihan sedangkan kelompok yang lain dijadikan kelompok kontrol. Hasil penelitian terdapat peningkatan vo2max untuk kelompok yang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Almost identical to the study which found that passive recovery with local lower extremity massage increased leg muscle strength more quickly when compared to passive recovery by sitting after a decrease after physical activity. (Helaprahara et al, 2022) [15] . Besides that(Mulya et al, 2021) [25] states that sport massage or sports massage can help improve blood circulation while stretching focuses on increasing muscle elasticity and range of motion and recommends that athletes apply sports massage regularly to reduce the risk of muscle fatigue and even muscle injury.…”
Section: Resultsmentioning
confidence: 99%
“…Almost identical to the study which found that passive recovery with local lower extremity massage increased leg muscle strength more quickly when compared to passive recovery by sitting after a decrease after physical activity. (Helaprahara et al, 2022) [15] . Besides that(Mulya et al, 2021) [25] states that sport massage or sports massage can help improve blood circulation while stretching focuses on increasing muscle elasticity and range of motion and recommends that athletes apply sports massage regularly to reduce the risk of muscle fatigue and even muscle injury.…”
Section: Resultsmentioning
confidence: 99%
“…Almost identical to the study which found that passive recovery with local lower extremity massage increased leg muscle strength more quickly when compared to passive recovery by sitting after a decrease after physical activity. (Helaprahara et al, 2022) [15] . Besides that(Mulya et al, 2021) [25] states that sport massage or sports massage can help improve blood circulation while stretching focuses on increasing muscle elasticity and range of motion and recommends that athletes apply sports massage regularly to reduce the risk of muscle fatigue and even muscle injury.…”
Section: Resultsmentioning
confidence: 99%